In Silico Analysis of Actin Gene as a Candidate for DNA Non-Halal Detection Base on Real-Time PCR - Waluyo, Seagames; Malau, Jekmal; Raekiansyah, Muhareva; Yulian, Edwin; Hardiman, Imam (Indonesian Journal of Halal Research, 2021)
Actin genes are genes that are common in organisms, and their expression is constitutive. These genes are used for gene normalization and internal control of DNA extraction, but the actin gene is not widely used for halal certification tests. Bioinformatic studies help to analyze the experiment through in silico more deeply before the experiment is carried out in laboratory, making it more efficient and time effective. uMelt is an analysis to predict the melting curve of target amplification in real-time PCR. Real-time PCR has been widely used for screening and detection of pork content in a product. This research aimed to explore actin gene as a candidate for testing pork using qPCR. The study was carried out in two main stages, namely alignment of the DNA sequence and analysis of the melting curve using the uMelt approach. The results showed a set of actin genes containing conserved regions that can be used as degenerate primers with different family-type coverages. Melting curve prediction with uMelt shows differences in tm peaks so as the types of samples can be easily identified. The use of bioinformatic applications such as uMelt helps in the simulation of predicting the melting curve to increase the precision of the analysis.